hii everyone
Please answer this question
Attachments:
![](https://hi-static.z-dn.net/files/dac/4f7aacd8a4e27c70f30c636028f7113e.jpg)
Answers
Answered by
1
Step-by-step explanation:
PLEASE MARK ME AS BRAINLIEST ANSWER
Attachments:
![](https://hi-static.z-dn.net/files/d2a/3492ff6f1bb9aad41021f072d9f9ac53.jpg)
Answered by
4
Solution:
Given ,
cotθ = 7/8
We need to find
(1 + sinθ)(1 - sinθ)/(1 + cosθ)(1 - cosθ)
Using
(a + b)(a - b) = a² - b²
→ 1² - sin²θ/1² - cos²θ
→ 1 - sin²θ/1 - cos²θ
We know that
1 - sin²θ = cos²θ
1 - cos²θ = sin²θ
Substituting we have
→ cos²θ/sin²θ
We know that
cosθ/sinθ = cotθ
→ cot²θ
→ (7/8)²
→ 49/64. [°.° Given , cotθ = 7/8]
Hence , (1 + sinθ)(1 - sinθ)/(1 + cosθ)(1 - cosθ)
Similar questions